Small‐Scale Machines Driven by External Power Sources - Chen, Xiang‐Zhong; Jang, Bumjin; Ahmed, Daniel; Hu, Chengzhi; De Marco, Carmela; Hoop, Marcus; Mushtaq, Fajer; Nelson, Bradley J.; Pané, Salvador (Advanced materials (Weinheim), 2018)
Micro‐ and nanorobots have shown great potential for applications in various fields, including minimally invasive surgery, targeted therapy, cell manipulation, environmental monitoring, and water remediation. Recent progress in the design, fabrication, and operation of these miniaturized devices has greatly enhanced their versatility. In this report, the most recent progress on the manipulation of small‐scale robots based on power sources, such as magnetic fields, light, acoustic waves, electric fields, thermal energy, or combinations of these, is surveyed. The design and propulsion mechanism of micro‐ and nanorobots are the focus of this article. Their fabrication and applications are also briefly discussed. Externally powered micro‐ and nanorobots are promising candidates for future biomedical applications. Recent progress on externally powered small‐scale robots is summarized based on their power sources. The emphasis is laid on the design and propulsion mechanism of the microrobots. The fabrication and application is briefly discussed as well.